Validation of an online questionnaire of vocabulary learning strategies for ESL learners - Gu, Peter Yongqi (Studies in Second Language Learning and Teaching, 2018)
This article reports on the updating and validation of a questionnaire for vocabulary learning strategies. An English as a second language (ESL) version of the Vocabulary Learning Questionnaire (VLQ), first published in Gu and Johnson (1996), was created based on its latest version. Two response formats were piloted, that is, a paper version with a 7-point Likert scale and an online version with a 100-point slider bar. A series of validation procedures resulted in a 62-item instrument which was then administered online among 682 English language learners at the tertiary level in China. The paper presents evidence of content validity, construct validity, internal consistency reliability, and predictive validity. It also provides suggestions for interpreting and using the questionnaire for both research and instructional purposes.